Prentice Hall explore it generation ([place of publication not identified Prentice Hall, 2001)
This CD-ROM contains 12 interactive student labs created in Macromedia Authorware. Choose a lab from the main menu screen by double clicking on it. Program will provide on screen instructions to complete each lab. For more information on Macromedia products you can visit www.macromedia.com
Building a Webpage -- Internet and WWW -- E-commerce -- Programming -- Application software -- Operating System -- Multimedia -- Building a network -- Buying a computer -- Hardware -- Files and folder -- Binary representation.
System Requirements: Pentium 166 processor, Windows 95, 98, 2000, NT4 and ME, 32 MB RAM/64 MB recommended (64 MB RAM/128 recommended for Windows 2000).
In English.
Keywords: Digital techniques; Computer